Pengaruh pengalaman ekonomi pada aplikasi pemasaran berbasis augmented reality terhadap kepuasan konsumen - Amanah, Dian Martha Nurrul (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
Augmented reality emerges as a form of technological advancement. Known with a rich visual technology, augmented reality is being adapted in various fields such as marketing, education, healthcare, military, sports, tourism, and others. In the business world, this 3D-based technology is believed to enhance the shopping experience of consumers, ultimately leading to customer satisfaction. This research was conducted to examine the influence of economic experience on satisfaction. Economic experience was divided into four categories: aesthetics, entertainment, learning, and escapism, where aesthetics served as a precursor to the other three components. The data collection process involved distributing online questionnaires to respondents who actively use smartphones and were required to try one of the five augmented reality marketing applications used in this study. The augmented reality marketing applications used in this research were Shopee (Beauty Cam), Sephora (Virtual Artist), IKEA Place, Dulux (Visualizer), and Kinder Joy (Applaydu). The study, conducted with 230 respondents in Indonesia, revealed that aesthetics has a positive influence on entertainment, learning, and escapism. Furthermore, entertainment, learning, and escapism have a positive influence on satisfaction.